TEACHER EDUCATION FOR SUSTAINABILITY-INSIGHTS INTO EVOLVING STUDENT TEACHERS ` IDENTITIES - Raus, Rea (European Scientific Journal, ESJ, 2013)
Teacher Education for Sustainability- Insights into Evolving Student Teachers` Identities The concept of sustainability is often discussed as an ecological, environmental concept but it is more complex and interdisciplinary concept. Ospina (2000) states that sustainability is not only a scientific concept, but more of a moral precept so when we discuss sustainable development of human societies, we come to the question of values and education. A teacher, his/her values, attitudes, personal philosophies form a lens through which learning-teaching process is approached to, therefore teacher identity is of particular interest in this research. My research has the central question- how future teachers can be assisted in becoming aware of their potential to construct their own identities for sustainable worldview and to become a teacher with a holistic understanding of the world as one ecosystem. The key focus is therefore on student teacher`s personal philosophies about sustainability in the framework of evolving teacher identity. The results should give recommendations for teacher education curriculum to support the construction of teacher professional and personal identity towards sustainable worldview, including the development of relevant practices to be implemented through teacher education studies. The ongoing research is a longitudinal qualitative research and takes the phenomenological approach, where the main methods are written narratives and in-depth interviews with case discussions. The sample includes a group of 9 student teachers (grammar school) to be studied over the 5 year period of initial teacher education programme.